Osteonecrosis of the jaws during biphosphates therapy of mieloma multiplex - Marcinkowski, Michał; Osmola , Krzysztof (Journal of Stomatology, 2017)
Introduction. Mieloma multiplex is a malignant, disseminated cancer of the hematopoietic system. This disease is a cause of numerous metabolic and systemic disturbances, which lead to defects in the osseous system as a single or numerous osteolytic lesions, which contribute to pain and pathological fractures, and in the end to patient’s disablement. Bisphosphates are the group of drugs which are used in treating mieloma multiplex leading to improvement of metabolism of osseous tissue by stimulating osteogenesis and thus reducing osteolytic foci. In recent years, there have been reports concerning adverse effects of bisphosphates therapy namely osteonecrosis of the jaws, especially of the mandible. These lesions are confused with mieloma multiplex foci, and are very difficult to treat. Aim of the study. To present the case of a 58-year-old woman who suffered from osteonecrosis of the jaws after many years of bisphosphates application used to treat mieloma multiplex. Conclusion. Bisphosphates have a favourable influence on the osseous system especially on bones of the vertebral column and pelvis, but they can induce side effects on long-term use. Recommendations for both for patients and physicians during bisphosphates therapy have also been outlined.